NITROGEN REQUIREMENT OF MAIZE IN POTATO + MAIZE INTERCROPPING SYSTEM IN SHIMLA HILLS - Lal, S. S; Dua, V. K; Govindakrishnan, P. M. (Potato Journal, 2013)
In potato + maize intercropping system at Shimla, maize responded only upto 75 kg nitrogen/ha when grown in 3:1 pattern with 100% and 25% of their respective sole crop populations. However, nitrogen dose to maize could not be revised and it still required full dose (100 kg/ha) when it was grown in 1:1 pattern with 50% population of sole potato and 75% population of sole maize.